Alia and the story of rose - "Jafri Adeeba" (india, Good word books, 2010)
The story follows Alia, a young girl who notices her mother wearing a hijab and wonders why. Through a simple narrative and vivid illustrations, the book explains the significance of the hijab in Islam, emphasizing modesty, identity, and faith. The story is designed to be accessible to young readers, providing an Islamic perspective on a common question.